Multiphoton Absorption of Myoglobin–Nitric Oxide Complex: Relaxation by D-NEMD of a Stationary State - Cottone G; Ciccotti G; Elber R.; LATTANZI, GIANLUCA (The Journal of Physical Chemistry B, 2012)
The photodissociation and geminate recombination of nitric oxide in myoglobin, under continuous illumination, is modeled computationally. The relaxation of the photon energy into the protein matrix is also considered in a single simulation scheme that mimics a complete experimental setup. The dynamic approach to non-equilibrium molecular dynamics is used, starting from a steady state, to compute its relaxation to equilibrium. Simulations are conducted for the native form of sperm whale myoglobin and for two other mutants, V68W and L29F, illustrating a fair diversity of spatial and temporal geminate recombination processes. Energy flow to the heme and immediate protein environment provide hints to allostery. In particular, a pathway of energy flow between the heme and the FG loop is illustrated. Although the simulations were conducted for myoglobin only, the thermal fluctuations of the FG corner are in agreement with the large structural shifts of FG during the allosteric transition of tetrameric hemoglobin.